If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6y-7-3y+3=0
We add all the numbers together, and all the variables
3y-4=0
We move all terms containing y to the left, all other terms to the right
3y=4
y=4/3
y=1+1/3
| 7a-3=3=3-2a | | 4^(3x-2)=5 | | 12s+s-13s+3s+3s=18 | | -40=13t | | -6u-22=-2(u+5) | | 20x-3=36+9 | | -8=-4k | | 12s+s-s13s+3s+3s=18 | | (x+5)=(5x-27) | | 3/4x+6=26-(1/2x+10) | | 3(-2x+4)=-4(2x-6) | | 6(y+2)=-48 | | 2x+x=5=-3x-5x=3 | | 10+3x=25+1x | | 7x+38=-6(5-4x) | | 1/5(-15w-20)+1/2(3-4=) | | 7x+2-3x=10-2x+4 | | -6-3m=-5m+6 | | 3x+15=2x-3x=-17 | | -17.2(82u-86)=-154.8(6u-22) | | (5y-5)-(9y-1)=-4y-4 | | 8(8x+7)=-8(x+2) | | 4(x-3)^2-100=0 | | 7x+4x-80=60-9x | | a/2=8-4/6 | | x+7/6=5/6(x) | | -4x+12=5x-15 | | -127=7(-3a-1)+6 | | 20+y=150 | | 8x+6x-36=90-4x | | 5(-7x+9)=-270 | | -8x=-13x-65 |